Robot Control - Gorrostieta Hurtado, Efren (IntechOpen, 2016)
This book includes a selection of research papers in robot control applications. The description of projects using robotic systems in areas such as vision, navigation, path planning, trajectories, non-holonomic systems, mobile robotics, robot control with very specific structures, as well as artificial intelligence systems is pointed out. It also presents several tools and mathematical concepts that allow the development and operation of robotic systems. Additionally, the development of different ideas in control systems that are useful and hopefully enriching for the reader are also presented in this book.